2015
DOI: 10.1027/1016-9040/a000208
|View full text |Cite
|
Sign up to set email alerts
|

Anorexia and Bodily Intersubjectivity

Abstract: One’s experiences of hunger, food, eating, and the body are not only subjective but intersubjective: They involve one’s relation to others. On the basis of this observation, what is proposed here is a conception of anorexia as bodily intersubjective: Anorexia would involve, via the manipulation of food and eating behavior, the transformation of the subject’s body, as a way of impacting her relations to others. The anorexic subject would instrumentalize her eating behavior and bodily shape to address others, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…as outside of her control (see Legrand & Briend 2015). Indeed, Englebert et al (2018) suggest that one way in which individuals with AN seek to avoid having control exerted over them by others, is to adopt food-practices where they are in control of providing food for others, thus ensuring they are not submitted to external command and vulnerability.…”
mentioning
confidence: 99%
“…as outside of her control (see Legrand & Briend 2015). Indeed, Englebert et al (2018) suggest that one way in which individuals with AN seek to avoid having control exerted over them by others, is to adopt food-practices where they are in control of providing food for others, thus ensuring they are not submitted to external command and vulnerability.…”
mentioning
confidence: 99%
“…The eating behavior and transformation of the subject's body play a role in the family relationship. The anorexia nervosa subject would use as a tool her eating disorder and bodily shape to address others, to manifest her distress or her desire, to put the others, and specially the parents, in a position to answer or to do something for her distress [15]. The study of Rothschild-Yakar et al [16] indicated that anorexia nervosa type patients presented significantly lower metallization levels and lower quality of current relationships with their parents compared with non-eating disorder controls.…”
Section: Adolescence and Family A Family Issue As Anorexia Nervosa Omentioning
confidence: 99%
“…The adolescent who searches for more autonomy, claims with conflict more independence, addresses to their parents to be taken care of by her eating disorder. Anorexia nervosa affects not only the subject's relation to food but also her relation to others [15] and especially to her parents.…”
Section: Adolescence and Family A Family Issue As Anorexia Nervosa Omentioning
confidence: 99%
See 2 more Smart Citations